Angiography in thoracic outlet syndrome. - Bogalho, L (1998)
The thoracic outlet syndrome is a changeable clinical syndrome caused by compression of the neurovascular bundle of the upper extremity, within the cervicoaxillary channel. From April 1980 through May 1995, 24 patients with clinical thoracic outlet syndrome were evaluated by selective arteriography. The diagnosis was confirmed in seven patients, in 14 the exam was normal and in the last three cases another arterial pathology was detected--subclavian artery occlusion, subclavian artery kinking and vertebral steal syndrome. The authors' aim is to emphasize arteriography as a diagnostic exam for thoracic outlet syndrome, very useful in the detection and localization of arterial compression. It also allows the diagnosis of other arterial entities.